Evaluación posterior a terapia de estimulación ortopédica maxilar temprano en niños con síndrome de Down - Rincón-R., Ramiro; Jiménez-B., Javier; Duque-E., Olga; Chaurra-M., Rosa Cristina (Revista Facultad de Odontología Universidad de Antioquia, 2020)
The purpose of this study was to identify the effects of early maxillary orthopedic treatment in children under one year of age with Downs syndrome, using a soft acetate plate with a palatal stimulator of the Castillo Morales type, that seeks to improve the lingual position by means of a exteroceptive stimuli. Study models, anthropometrical measurements and film registrations were taken to a group of 34 children. Cranial and facial changes as well as changes in the dental arches were evaluated during 6 months. The children that received the therapy showed an improvement in the lingual position, some of them even presented labial seal; they also showed larger facial dimensions in the following anthropometrical measurements: face height, byzigomatic diameter, bigonial diameter, and facial index. The measurements in the study models did not show any statistically significant differences between the treatment and the control group. Younger patients adapted better to the plate, which indicates that the therapy could be more favorable if it is initiated at an early age. Quantitative changes (anthropometrical, and model evaluation) and qualitative changes (video and parents opinion) were observed with the early maxillary orthopedic treatment and it produces improvement in function and cranial facial development in children with Down’s syndrome